THE DYNAMICS OF SUNNI-SHIA RELATIONS IN THE CITY OF A THOUSAND CHURCHES MANADO - Taufani Taufani; Muh. Natsir; Nurman Said; Andi Aderus (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
This article aims to discuss dynamics of the Sunni and Shia relations in Manado. The data were collected from interviews, observation, and documentation. This study shows that the Sunni and Shia Muslim relations in Manado lived in harmony at the grassroots level. They lived next door, visited, and also helped each other in various matters. However, the relations between Sunni and Shia had been in tension due to anti-Shia campaigns by local Sunni elites and Salafi-Wahabi groups in the public sphere that took advantage of the momentum of the Sunni-Shia conflicts in the country and also the Middle East. They also took advantage of the particular political events deemed to benefit the Shia’s existence. Although the Shia groups had become the target of hatred, it did not result in physical violence. The abuse that occurred on the Shia was of verbal and symbolic. This study concludes that the minority status does not always lead to a harmonious relationship within its own internal group.